O corpo da palavra literária sob o olhar impressionista da pintura, em A carne de Júlio Ribeiro - Pereira, Elizandra (2009)
This paper has as its aim analyzing the novel A CARNE, by Júlio Ribeiro (1888), according to the Impressionist painting view, in order to revalue it while an esthetic object, under the Naturalism and Impressionism conceptions. The first chapter deals with the analysis perspective which is able to verify the inter-relations between image and word in tension areas of the narrative between narration and description. This favors, at the same time, the perception and the observation of the word that is being read through the application of the artistic and impressionist proceedings on the literary discursive material. The second chapter enlights new possibilities for the plastic-visual articulation, materialized in the literary word by considering the impressions and sensations of the real world as an object. By means of the reflection on the real, the Impressionist artist Claude Monet used to project his painting diagrams on the screen. This way, Júlio Ribeiro s literary word is delegated to the narrator under two proceeding aspects: the scene told as word and the scene shown as image. The third chapter shows that the tension zones are crossed sometimes by the narrator s view and others by the character s one, resulting in the dissociation subject-object in the literary discourse. This is what bases the synthesis word-object beneath the Impressionist perspective between the artist and/or writer s reflections and depuration. In the conclusion, it is finally detached that in A CARNE , by Júlio Ribeiro, the image, together with the word in experimentation, receives an artistic function of presenting the body of the word-object, to the reader, to the literature understood as word-body in an acting of representing the real